Enhancing Employee Performance Through Organizational Climate and Job Satisfaction: Evidence from a Private University - Dijah Julindrastuti; Iman Karyadi (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
Employees play an important role in determining organizational success. A positive organizational climate and high job satisfaction are expected to improve employee performance and support organizational growth. This study aims to analyze the influence of organizational climate on employee performance with job satisfaction as a mediating variable. The research was conducted on non-academic employees at a private university “X”. The sample consisted of 50 employees with a minimum working period of 20 years, selected using purposive sampling techniques. Data were analyzed using Structural Equation Modeling (SEM) with AMOS 16.0 to examine the mediating role of job satisfaction.The results show that organizational climate has a significant effect on employee performance (p = 0.000). Job satisfaction also significantly affects employee performance (p = 0.000). However, organizational climate does not significantly influence job satisfaction (p = 0.154), and job satisfaction is not able to mediate the relationship between organizational climate and employee performance (p = 0.214). These findings indicate that improving organizational climate directly contributes to better employee performance, while job satisfaction does not function as an intervening variable in this relationship. The study highlights the importance of creating a supportive organizational climate to enhance employee performance in higher education institutions.